A rare case of Gitelman syndrome in a 37-year-old male - Sinha, Nishant; Sahu, Ramsewak; Sharma, Pragya (Indian Journal of Case Reports, 2020)
Hypokalemia refers to a deficiency of potassium in the bloodstream with or without clinical signs and symptoms. It is a common electrolyte disbalance found in all age groups. There are many causes of hypokalemia and though rare but certain renal tubular channelopathies as Gitelman syndrome (GS), Bartter syndrome, and Liddle syndrome can also be manifest with altered arterial blood gas, blood pressure, and hypokalemia. In the presented case, a 37-year-old man with generalized weakness, muscle cramps, and hypotension was found to have hypokalemia. Ruling out the possible common causes of hypokalemia with hypotension and alkalotic pH and his resistance to potassium replacement was investigated for renal tubular channelopathies. He was found to have blood and urinary parameters favoring GS. He showed marked improvement in his symptoms on Aldactone. This has opened our minds to try to see for these channelopathies as potential causes of hypokalemia and improvement of the same on addressing the defect.